Use of Washington State newspapers for submersion injury surveillance. Issue 4 (1st December 2001) - Baullinger, J; Quan, L; Bennett, E; Cummings, P; Williams, K
Abstract : Objectives —To evaluate the usefulness of newspapers as a surveillance tool for submersion injury, the proportion of submersion events and important details reported in Washington State newspapers was determined. It was also determined whether a letter sent to newspaper editors to encourage reporting changed the proportion and content of reported submersion events. Methods —Newspaper articles regarding submersion were collected from 225 Washington newspapers from June 1993 through September 1998. Newspaper articles were linked to computerized state death and hospital records. Reporting during periods before and after a letter was sent encouraging more newspaper articles on submersion injury and preventative factors was compared. Results— A total of 1874 submersion victims were identified in the three data sources. Of the 983 victims who had a death certificate, 52% were reported in at least one news article. Of the 471 persons in hospital discharge data, 25% were reported in a newspaper. Reporting of pediatric victims who died increased from 63% to 79% (p=0.008); reporting of hospitalized persons increased from 23% to 27% (p=0.3). There were increases in reporting of swimming ability (7% to 15%, p<0.001), supervision (82% to 91%, p<0.001), and alcohol use (7% to 24%, p<0.001). Reporting of life vest use decreased (35% to 23%, p<0.001). Conclusions —Newspapers failed to report about one half of fatal submersions and three quarters of submersions that resulted in a hospitalization. An effort to improve reporting was associated with an increase in the proportion of pediatric drownings that were reported, but a consistent improvement in content was found. The usefulness of newspaper articles as a surveillance tool may be limited.